Renal dendritic cells: an update. - Velázquez, P; Dustin, M; Nelson, P (2009)
Discovery into the role of renal dendritic cells (rDCs) in health and disease of the kidney is rapidly accelerating. Progress in deciphering DC precursors and the heterogeneity of monocyte subsets in mice and humans is providing insight into the biology of rDCs. Recent findings have extended knowledge of the origins, anatomy and function of the rDC network at steady state and during periods of injury to the renal parenchyma. This brief review highlights these new findings and provides an update on the study of rDCs.